DECISION MAKING DECISION MAKING BASED ON FUZZY PREFERENCE RELATIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Many fuzzy versions of common multi-criteria decision making (MCDM) methods have been proposed to date. Among these methods, a special place is occupied by the method based on fuzzy preference relations (FPR). This method is fuzzy in nature and has no crisp analogue. The essence of the method is to evaluate preferences on pairs of alternatives. The source for evaluation is subjective judgments of expert specialists based on their knowledge and experience. The purpose of this article is to present in detail and clearly the theoretical foundations of this specific method in the context of multi-criteria decision making under conditions of highly uncertain initial information. Based on the initial assignments of the experts, using relevant computational procedures, the resulting preference scores for each of the alternatives are determined. These resulting scores are the basis for selecting the optimal alternative or ranking the alternatives by preference. The article presents two alternative versions of this method. The article presents three illustrative examples, whose purpose is to demonstrate the relevant computational procedures.